Addictive Behaviors: Readings on Etiology, Prevention, and Treatment. 1997
DOI: 10.1037/10248-023
|View full text |Cite
|
Sign up to set email alerts
|

Matching treatment focus to patient social investment and support: 18-month follow-up results.

Abstract: In recent years, there has been an increasing focus in psychotherapy research toward identifying combinations of patient and treatment factors that increase treatment effectiveness (butler, 1991;Blatt & Felsen, 1993; Dance & Neufeld, 1988). As indicated by an examination of attributetreatment interactions conducted previously in educational testing research (Cronbach & Snow, 1977), such study requires sophistication in research Reprinted from the J o u d of Consulting and Clinical Psychology, 63, 296-307. (19… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
52
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(56 citation statements)
references
References 20 publications
4
52
0
Order By: Relevance
“…Social investment was predictive of less heavy drinking during treatment. Social investment has been previously found to relate to drinking (Longabaugh et al, 1993a), although this relationship may be complex (Longabaugh et al, 1995) or inconsistent (Groh et al, 2007a;Zywiak et al, 2002). The relationships of measures of general support to drinking are understandable, perhaps in the context of an alcohol-dependent patient who is entering treatment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Social investment was predictive of less heavy drinking during treatment. Social investment has been previously found to relate to drinking (Longabaugh et al, 1993a), although this relationship may be complex (Longabaugh et al, 1995) or inconsistent (Groh et al, 2007a;Zywiak et al, 2002). The relationships of measures of general support to drinking are understandable, perhaps in the context of an alcohol-dependent patient who is entering treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Whereas general support promotes overall well-being, alcohol-specifi c support is directly tied to alcohol use Longabaugh, 1997, 1999;Beattie et al, 1993;Longabaugh and Beattie, 1986). The Important People and Activities (IPA) instrument was developed to measure structural and functional dimensions of alcohol-specifi c support in a patient's social network (Longabaugh et al, 1993a(Longabaugh et al, , 1995. A later version of the IPA was used in Project MATCH (Matching Alcoholism Treatments to Client Heterogeneity;.…”
mentioning
confidence: 99%
“…This may be because, in the eyes of these social network members, these particular subjects were not perceived to be stereotypically alcoholic. Thus, there may be an important opportunity to intervene with these individuals to see if they can be converted to "white hats"; broader public health message initiatives might need to focus on dispelling the commonly held "skid row" alcoholic stereotypes (Litt et al, 2009;Longabaugh et al, 1995Longabaugh et al, , 2010.…”
Section: Discussionmentioning
confidence: 99%
“…However, this undesirable relationship is dependent on what type of alcohol treatment one receives. Longabaugh et al (1995) indicated that, for clients with social networks supportive of drinking, receiving a treatment with the goal of decreasing support for drinking or increasing support for abstinence will be effective in improving subsequent alcohol treatment outcomes. The results of the current study provide further empirical evidence for client-treatment matching.…”
Section: Discussionmentioning
confidence: 99%